Dynamic study of a battery change-over scheme of a windfarm containing dual BESS - Yao, D.; Choi, San Shing; Tseng, K.; Lie, T. (2012)
The wind farm-dual-battery energy storage systems (BESS) described in [1] is studied in greater detail for those instances when the battery banks change-over. The primary design objective of the wind farm-BESS scheme is to realize the dispatchability of wind generation. The scheme requires two BESS modules to inter-change between charging-discharging modes. A new power flows control strategy is designed to cater for the battery switching-over operation while practical constraints on the charging-discharging of the BESS are considered. A dynamic study is included to illustrate the strategy. © 2012 IEEE.